UWB down-conversion mixer using an IM3 cancellation modified technique for zero and low IF applications. (March 2021) - Seyedi, Hosein; Dehdasht-Heydari, Ramin; Roshani, Saeed
Abstract: In this paper, an UWB down-conversion mixer is presented with high 3rd order linearity. The UWB bandwidth of the mixer can be achieved in 0.9–5 ​GHz by using a cascode structure with four capacitors. These capacitors are used to make a feedback network for IM3 cancellation in transconductance stage of active double-balanced Gilbert mixer cell. By using this novel technique, a maximum IIP3 of 20.5 dBm is obtained in IF frequency of 1 ​MHz and this mixer can be applied for direct conversion receivers (DCRs). Furthermore, the proposed mixer can work up to IF frequency of 100 ​MHz for low-IF applications. The conversion gain is about 11.3 ​± ​0.5 ​dB with 16.9 ​dB NF in IF frequency of 1 ​MHz. The power consumption is 3.5 ​mW from a 1.2 ​V power supply. The schematic of the designed mixer is simulated in 65 ​nm RF TSMC CMOS technology with Cadence IC Design tools and also was analyzed and compared with Volterra series for more accuracy. The dimensions of the mixer's layout are roughly 391 μ m × 132 μ m .